The unusual behavior of Galactose-Steroid Bingel-Hirsch reaction for functionalization of C60-fullerene: a theoretical study - Aldás Bedón, Jhonny Mauricio (2022)
The [60] fullerene is a molecule that has been functionalized to modify its chemical properties such as solubility and explore its biological and materials science applications. It has been exohedrally functionalized with hydrophilic groups, i.e., amino acids, peptides, steroids and sugars, which improves its hydrophilicity and biocompatibility. The Bingel-Hirsch reaction is an efficient tool for the regioselective cyclopropanation of C60 to methanofullerene, starting from malonic esters derivatives, 1,8-Diazabicyclo[5.4.0]undec-7-ene (DBU) as base and carbon tetrabromide (CBr4). It is an alternative strategy to the Bingel reaction, proposing the generation of the reactive monohalomalonate intermediate in situ. Herein, a Bingel-Hirsch reaction of D-galactose-diosgenin malonic ester derivatives is studied. The results showed that the awaited product suffers the ester hydrolysis promoting the Galactose release, followed by decarboxylation to obtain a Diosgenin-C60 hybrid. The full characterization of the final product through IR, NMR, and MALDI-TOF spectrometry is presented. Based on the experimental results, a plausible mechanism is proposed in which a DBUH+ or traces of H3O+, both possible byproducts in the Bingel-Hirsch procedure, to donate a proton to improve the observed acid-catalyzed hydrolysis through a unimolecular alkyl cleavage AAL1 mechanism because the highly stable galactose cation release. Theoretical calculations at the DFT PBE/6-31G level of theory predict the most stable structural geometries for all compounds involved in the proposed mechanisms. Relevant stereoelectronic parameters were investigated considering selected descriptors and properties, namely polarizability, dipole moment, lipophilicity, and topological polar surface area, showing that the hydrolysis and subsequent decarboxylation do not cause drastic changes in the properties analyzed. In addition, the PM3 semi-empirical method is used to calculate the Potential Energy Profile (PEP) of the acid-catalyzed hydrolysis of the galactose-diosgenin-fullerene hybrid by DBUH+ or H3O+ in the gas phase. According to the PEP, it is observed that hydrolysis responds to a bimodal process, and is thermodynamically favored with H3O+.